Agar with embedded channels to study root growth - Aziz, Azlan Abdul; Lim, Kai Boon; Rahman, Ena Kartina Abdul; Nurmawati, Muhammad Hanafiah; Zuruzi, Abu Samah (Scientific reports, 2020)
Agar have long been used as a growth media for plants. Here, we made agar media with embedded fluidic channels to study the effect of exposure to nutrient solution on root growth and pull-out force. Black Eye bean ( Vigna Unguiculata ) and Mung bean ( Vigna Radiata ) were used in this study due to their rapid root development. Agar media were fabricated using casting process with removable cores to form channels which were subsequently filled with nutrient solution. Upon germination, beans were transplanted onto the agar media and allowed to grow. Pull-out force was determined at 96, 120 and 144 h after germination by applying a force on the hypocotyl above the gel surface. The effect of nutrients was investigated by comparing corresponding data obtained from control plants which have not been exposed to nutrient solution. Pull-out force of Black Eye bean plantlets grown in agar with nutrient solution in channels was greater than those grown in gel without nutrients and was 110% greater after 144 h of germination. Pull-out force of Mung bean plantlets grown in agar with and without nutrient solution was similar. Tap root lengths of Black Eye bean and Mung Bean plantlets grown in agar with nutrient solution are shorter than those grown without nutrient.